SENSITIVITY PATTERNS AND SHIFTS IN MICROBIAL SENSITIVITY TO ANTIBIOTICS IN THE INTENSIVE CARE UNIT OF ADVENT HOSPITAL BANDUNG - Laurencia, Aubrey
Antimicrobial resistance remains a global issue with significant impacts on high morbidity rates, mortality, prolonged treatment duration, and the overall cost of healthcare. The pattern of resistance and shifting sensitivities is one of the strategies of the Antimicrobial Resistance Control Program (PPRA) in hospitals to prevent a microbial resistance pandemic. This study aims to analyze the patterns of resistance and sensitivity shifts of antimicrobials in the Intensive Care Unit of Advent Hospital Bandung. This research was conducted descriptively and retrospectively from June to August 2023. Data on microbial patterns and resistance patterns were collected from the years 2020, 2021, and 2022. Five Gram-negative bacteria, five Gram-positive bacteria, and one fungus were selected for analyzing sensitivity shifts. Statistical analysis using a T-test was performed to assess the significance of sensitivity shifts with a p-value of <0.05. From the data analysis, it was found that the most common specimen was sputum (69.95%). The most prevalent Gram-negative bacteria were A. baumannii [Carbapenem Resistant] (13.64%), K. pneumoniae (13.64%), P. aeruginosa (8.22%), K. pneumoniae [Carbapenem Resistant] (5.77%), Acinetobacter sp. [Carbapenem Resistant] (4.72%), and the most common Gram-positive bacteria were S. aureus (23.24%), S. pyogenes (8.11%), S. epidermidis [CoNS] (5.95%), S. haemolyticus [CoNS] (5.95%), S. pneumoniae (2.16%), and the fungus Candida albicans (40%). The statistically significant microbial shifts towards antimicrobial resistance from sensitive to non-sensitive include Klebsiella pneumoniae, Staphylococcus pyogenes, Staphylococcus epidermidis [CoNS], Staphylococcus haemolyticus [CoNS], Candida albicans. Conversely, the statistically significant microbial shifts towards antimicrobial sensitivity from resistance include Acinetobacter baumanii [Carbapenem Resistant], Acinetobacter sp. [Carbapenem Resistant], Klebsiella pneumoniae [Carbapenem Resistant], Staphylococcus aureus, Streptococcus pneumonia.